A study on the relationship between money supply and stock market in Malaysia / Norotiny Harun - Harun, Norotiny (Faculty of Business and Management, 2010)
This study examines the relationships between money supply and stock market in Malaysia with the particular attention to the August 2007 until 2009 global financial crisis. Extending related empirical studies, comparative analyses of pre-crisis, crisis, and post crisis periods are conducted to comprehensively evaluate how stock market integration is affected by financial crises. In general, the results show that negative relationships between money supply and stock market in Malaysia. Money Supply changes have significant effect on stock market in Malaysia. In addition to this, money supply is one of the macroeconomic variables that will explain stock market in Malaysia. In this paper Regression Analysis approach was used to determine the significant relationship between money supply and stock market in Malaysia by way of analyzing the trend of the money supply and stock markets for the period January 2005 to August 2010.Monthly data were used for the analysis. The result show that there is a relationship between money supply and stock market in Malaysia.